Exploring teacher practices of ICT integration in the Classroom at Banda Aceh public schools - Ramadhani, Fithri (Kulliyyah of Education, International Islamic University Malaysia, 2018)
This study aimed to explore secondary public school teachers' perceived ICT competency, perceived competency in integrating ICT into the classroom and their attitudes towards ICT. Furthermore, this study was carried out to examine the extent of ICT integration in their teaching practices as well as to identify which variable influences the actual ICT integration the most. This quantitative study applied a cross sectional survey method for data collection where a total of 177 teachers from six public secondary schools at Banda Aceh, Indonesia took part as respondents. The questionnaire was developed on the basis of two previous studies by Aslan & Zhu (2016) and Peralta & Adriano (2013). The collected data were analysed by using Descriptive Analysis and Multiple Regression Analysis. The finding of this study revealed that public school teachers in Banda Aceh did not perceive themselves highly competent in ICT skills and they did not integrate much of the available ICT facilities in their teaching practices even after having a highly positive attitude towards ICT. The finding of regression analysis indicated that perceived competency in integrating ICT into classroom was a strong influence whereas attitude towards ICT did not show any influence at all. Moreover, results of this study will provide information for schools management and stakeholders as well as the policy makers under the local and central government and especially the Ministry of Education in Aceh to support the teachers fully to upgrade their skills in using ICT in their teaching practices. Besides, some recommendations for future research were also provided by the researcher in order to give relevant directions to teachers and policy makers for integrating ICT in any educational setting.